The Importance of Village Fund Management in Improving Community Welfare in Wadio Village, West Nabire District, Nabire Regency - Eduard Lodewik Pesiwarissa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Village Fund is mostly used for the development and administration of the village government, in its development, the village has now developed into various forms of empowerment so that it becomes an independent village. Objectives The effort to find out what the people of Wadio village do. The method used in this research is descriptive. The results showed that the total population of Kampung Wadio recorded in 1982 was 1,703 people with 583, the Village Head (KK) spread over four (4) Hamlet heads consisting of (867) males while (836) females. village funds have not been met directly and are enjoyed by the village community in Wadio village.